Reliability and Validity of the Preschool Science Observation Measure. Issue 2 (17th February 2019) - Vitiello, Virginia E.; Whittaker, Jessica V.; Mulcahy, Christina; Kinzie, Mable B.; Helferstay, Laura
ABSTRACT: Research Findings : Although interest in preschool science is growing, there are few observational measures of science teaching capable of advancing research or supporting professional growth among teachers. To address this gap, the current article presents the development and validation of the Preschool Science Observation Measure (PSOM), which assesses science teaching quality and the content of instruction for structured science lessons in preschool. Within the context of a randomized field trial of a science curriculum, 115 teachers submitted videos of science lessons and 1, 003 children ages 4 and 5 years old were assessed on their science skills in the fall and spring. Results indicated adequate range and reliability of PSOM scores. PSOM scores showed moderate positive associations with an observation of teacher–child interactions. Limited positive associations with children's science outcomes indicated some evidence of predictive validity. Descriptive results from control classrooms indicated wide variability in the content and quality of science teaching in typical preschool classrooms. Practice or Policy : Results support further development and use of the PSOM to evaluate science teaching quality and highlight the need for more research on science in preschool classrooms.